Influence of Moisture Content on Physical and Mechanical Properties of Cedrelinga catenaeformis Wood - Zanini Ribeiro Soares, Larissa Soriani (2021)
This study aimed to investigate the influence of moisture content variation on 12 mechanical properties of the Cedrelinga catenaeformis species. Of the 12 properties, four were significantly affected (based on analysis of variance at 5% significance level), and the compression and shear strengths in the direction parallel to the fibers exhibited the greatest difference in values from the saturated moisture condition of up to 12% (approximately 34% increase). Toughness exhibited a behavior different from that predicted by the normative equation, in which increase in moisture content implied increase (approximately 59%) of the property studied. Because a good part of the properties was not significantly affected and Brazilian standard ABNT NBR 7190 (1997) considers expressions that lead to a considerable increase in mechanical properties with the reduction of moisture content, this approach was unfavorable to the safety of the project, motivating the development of other studies to collaborate in revisions of this normative document.